Cervical cancer screening in developing countries : report of a WHO consultation (World Health Organization, 2002)
This publication is the product of a comprehensive consultation undertaken by WHO in 2001, involving leading experts in the field of cancer epidemiology, screening and treatment. It is part of WHO's commitment to provide evidence-based guidelines to decision makers and a recognition of the priority that should be given to cervical cancer screening and treatment as an essential component of any comprehensive national cancer control programme. The report focuses particularly on the situation in low and middle income countries - countries in which cervical cytology screening may not be feasible o.